THE IMPLEMENTATION OF THE INTERACTIVELEARNING MEDIA IN TEACHINGSPEAKING TO YOUNG LEARBERS(A Qualitative study of Beginner Grade Student in English for Young Learners Class) - Lukman Hakim, - (2011)
This study examines the implementation of interactive teaching media in the EYL class of Language Center of UPI. Three students from beginner level were involved as participants. The research used qualitative approach, specifically, using case study design. The data were obtained through participant observations and interviews. The finding shown that the speaking type, on the basis of Brown' speaking type, was dominated by responsive speaking type. Even so, every two meetings, the responsive speaking type suffered reductions. The encountered problems by teacher were related to the technical and the lesson issues. Meanwhile, even though the students' responses were conclusively positive, negative responses dominantly had occurred more in the initial meeting.